East Indian huts, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Some East Indians outside wooden huts.
Colour: Sepia (print); Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Huts--Trinidad and Tobago; Dwellings--Trinidad and Tobago; East Indians--Trinidad and Tobago; Ajoupa